The interplay of FLT3 and CXCR4 in acute myeloid leukemia: an ongoing debate - Klement, Laura; Drube, Julia (Frontiers in Oncology, 2023)
FLT3 mutations are very frequent in AML and utilization of FLT3 inhibitors as approved treatment options are very common. Despite the initial success of inhibitor treatment, the development of resistances against this treatment is a major challenge in AML therapy. One of the mechanisms causing resistance is the homing of the leukemic cells in the protective niche of the bone marrow microenvironment (BMM). A pathway mediating homing to the BMM and leukemic cell survival is the CXCL12/CXCR4 axis. The analysis of patient samples in several independent studies indicated that FLT3-ITD expression led to higher CXCR4 surface expression. However, several in vitro studies reported contradictory findings, suggesting that FLT3-ITD signaling negatively influenced CXCR4 expression. In this commentary, we provide an overview summarizing the studies dealing with the relationship of FLT3 and CXCR4. Taken together, the current research status is not sufficient to answer the question whether FLT3 and CXCR4 act together or independently in leukemia progression. Systematic analyses in model cell systems are needed to understand the interplay between FLT3 and CXCR4, since this knowledge could lead to the development of more effective treatment strategies for AML patients.